Exploring Brand Relevance: Gender Perspectives and Product Category Variances in Pakistan - Khan, Hameed; Farooq, Abdul (Journal of Business and Economic Options, 2021)
This study delves into new dimensions of brand relevance, focusing on understanding the significance of brands in influencing consumer purchase behavior and decision-making processes. While previous research has emphasized the role of brand relevance in determining the success of new products, there remain unexplored areas in this field. The study adopts Brand Relevance in Context (BRiC) as its framework, with a particular emphasis on gender perspectives. Additionally, it compares brand relevance across six product categories in Pakistan. The results of the study provide compelling evidence supporting the chosen BRiC measures for conducting cross-category and cross-gender comparisons. It is revealed that gender differences indeed impact brand relevance in certain product categories, while their influence may be similar in others. Moreover, cross-category comparisons shed light on the variability of brand relevance across different product categories. While some categories exhibit similar impacts on brand relevance, others show significant variation. The findings of this study hold valuable implications for managers and marketers in navigating the complexities of brand investments and market dynamics. By understanding the nuances of brand relevance across genders and product categories, managers can make informed decisions to minimize risks associated with brand investments and optimize marketing strategies. Ultimately, this study contributes to a deeper understanding of consumer behavior and brand dynamics in the Pakistani market, paving the way for more effective brand management practices.